Penghambatan Pertumbuhan Jamur Fusarium oxysporum Schlecht Pada Batang Padi (Oryza sativa L.) Menggunakan Ekstrak Metanol Umbi Bawang Mekah (Eleutherine palmifolia Merr.) - Mukarlina, Nuryanti Diana, Siti Khotimah, (Universitas Tanjungpura, 2014)
The wilt disease caused by Fusarium oxysporum Schlecht is a constraint in the cultivation of rice (Oryza sativa L.). This study aim was to determine the potential of the methanol extract of mekah onion (Eleutherine palmifolia Merr.) bulbs as antifungal for F. oxysporum. The fungi was isolated from rice stem samples that showed symptoms of Fusarium wilt disease. Fungi isolation was done through direct planting method and the test of antifungal inhibition capability was done by solid dilution method through poisoning food. The test results showed that the methanol extract of mekah onion bulbs contain secondary metabolites are able to inhibit the growth of of F. oxysporum colonies. Concentration of 62.5% has significant effect on inhibiting the growth of F. oxysporum.